Lymph node dissection for upper tract urothelial carcinoma: A systematic review - Chan, Vinson Wai-Shun (Arab J Urol, 2020)
OBJECTIVE: To perform a systematic review, according to the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) statement, investigating the role of lymph node dissection (LND) during nephroureterectomy (NU) for upper tract urothelial carcinoma (UTUC); focussing on survival and complication outcomes. METHODS: A comprehensive systematic search was completed using a combination of Medical Subject Headings terms and keywords related to UTUC and LND on multiple databases. Meta-analyses were performed when outcomes were reported under the same definition in two or more studies. Where meta-analysis was not possible, outcomes were reviewed in a narrative manner. RESULTS: A total of 21 studies were included in the qualitative analysis and 11 cohort studies in the quantitative analysis. Our review did not detect significant improvement in recurrence-free survival (RFS) (hazard ratio [HR] 0.89, 95% confidence interval [CI] 0.41–1.92), cancer-specific survival (CSS) (HR 0.89, 95% CI 0.54–1.46) and overall survival (OS) (HR 1.10, 95% CI 0.93–1.30). However, when focussing on studies only including patients with pT2/pT3 UTUC, not performing LND significantly worsened RFS (HR 2.83, 95% CI 1.72–4.66). Reports of removing more than eight lymph nodes may also provide prognostic benefits in pN0 patients. The performance of LND was not associated with a higher rate of postoperative complications (risk ratio 1.06, 95% CI 1.00–1.13). CONCLUSION: Overall, LND did not provide additional benefit in RFS, CSS and OS. However, there was a potential benefit in RFS in patients with muscle-invasive and advanced UTUC. LND was also not associated with increased risks of postoperative complications. Abbreviations: CIS: carcinoma in situ; CSS: cancer-specific survival; HR: hazard ratio; LND: lymph node dissection; NU: nephroureterectomy; OS: overall survival; PRISMA: Preferred Reporting Items for Systematic Reviews and Meta-Analyses; RFS: recurrence-free survival; RoB, risk of bias; RR: risk ratio; (UT)UC: (upper tract) urothelial carcinoma